PATTERN OF SPACE DAN PERILAKU BERMAIN ANAK SEKOLAH SELAMA PENDIDIKAN JARAK JAUH (PJJ) - Cardiah, Tita; Sudarisman, Irwan; Natasya, Egha Fauzia; Putri, Amelya Rahmadani; Senawianto, Alif Nurrahiim; Andiyan, Andiyan (Jurnal Arsitektur ARCADE, 2021)
Abstract: Learning activities for school children during the Covid-19 pandemic were carried out using the Distance Learning method. Distance learning indirectly changes children's behavior both while studying and playing. The restriction of activities and play space for school children during Distance Learning method is a change that all children must face, including children living in housing. Pattern of Space and environmental settings, especially the residential environment, have a major influence on children's playing behavior. This study uses a qualitative descriptive method, which is to analyze through comparison of survey data and direct observation from two different residential environment settings. The result of the research is that different spatial patterns will affect children's play behavior patterns during distance learning, children's responses to spatial patterns, structure and character of environmental settings in play activities. The behavior and responses of different children become the design reference and produce basic data about the effect of pattern of greeting on children's playing behavior. Subsequent research on elements of the playroom in the New Normal.Abstrak: Kegiatan pembelajaran anak-anak sekolah pada masa pandemik Covid 19 ini dilaksanakan dengan metode Pembelajaran Jarak Jauh (PJJ).  Pembelajaran Jarak Jauh secara tidak langsung merubah perilaku anak baik saat belajar maupun saat bermain. Pembatasan kegiatan dan ruang bermain anak-anak sekolah selama Pembelajaran Jarak Jauh merupakan suatu perubahan yang harus dihadapi  semua anak-anak termasuk anak-anak yang tinggal di Perumahan. Pattern of Space dan setting lingkungan khususnya lingkungan perumahan berpengaruh besar terhadap perilaku bermain anak. Penelitian ini menggunakan metode deskriptif kualitatif yaitu menganalisis melalui komparasi data hasil survey dan observasi langsung dari dua setting lingkungan perumahan yang berbeda. Hasil penelitian adalah pola ruang yang berbeda akan mempengaruhi pola perilaku bermain anak-anak selama pembelajaran jarak jauh, respon anak-anak terhadap pola ruang, struktur dan karakter setting lingkungan dalam kegiatan bermain. Perilaku dan respon anak-anak yang berbeda menjadi acuan desain dan menghasilkan dasar data tentang pengaruh pattern of sapace terhadap perilaku bermain anak.  Penelitian selanjutnya mengenai elemen ruang bermain dimasa New Normal.